‘I Look for my Father’s House’: Afro-Christian Spatiality of African Pentecostal Migrant Churches in Flemish Belgium - Bangura, Joseph Bosco (Studies in world christianity, 2026)
Flemish Belgium, much like the rest of western Europe, has seen migration increases with corresponding rise in anti-immigrant sentiments. While autochthone Protestant-Evangelical minority churches have responded and offered solidarity to immigrants, research has ignored African Pentecostal churches who, using Afro-Christian spatiality worldviews, have offered solidarity interventions to migrants. Predicated on African Pentecostalism’s belief in the church as ‘my father’s house’, this paper argues that by deploying this image, migrants are able to confront and resist marginality to positively reframe and reconstruct Pentecostal identities ruptured by displacement, migration and integration. The article contends that doing justice to African Pentecostalism’s reimagination of my father’s house requires taking account of what is at the heart of their Afro-Christian place-making initiatives, that is, the affirmation, recognition and reconciliation they seek with God and all humanity.